Política pública cultural. Una lectura a los equipamientos culturales como opciones de ocio en la ciudad de Medellín (2011)
ABSTRACT: This article presents the main results of the research: characterization of the users of cultural facilities in the city of Medellín, in particular the Community 10 (La Candelaria). A reconversion of Medellin was found, reconfigured as a city enterprise, organizer of great local and international events, which aims to attract tourists from health, business, academic and executive fields. Thus we understand the transformation and restoration of the urban area, including cultural facilities which extend the offer for the cultural consumption of them. There is a structural economic crisis of the facilities that has a direct relationship with the general crisis of the national state, who is trying to solve, overstating its regulation from a proliferation of regulations in cultural policies. Culture appears there, as a tool and not as an end, where there are irregularities and imbalances in the plans and projects, reflecting the absence of state leadership. Having a comprehensive view of cultural dynamics in Colombia, demands the assumption of a project to raise the inventory or a census of the cultural facilities that make up the cultural infrastructure of the country; no doing this, make difficult the knowledge of the projects that are being developed in different regions of the nation.